2018
DOI: 10.1080/21645515.2018.1540807
|View full text |Cite
|
Sign up to set email alerts
|

The safety of inactivated influenza vaccines in pregnancy for birth outcomes: a systematic review

Abstract: Pregnant women are at increased risk of morbidity and mortality from influenza and are recognized as a priority group for influenza vaccination. Despite this, uptake is often poor and one reason cited for this is concerns about safety. The objective of this study was to perform a systematic review of the safety of inactivated influenza vaccination (IIV) in pregnancy. Studies were included if they were: (i) observational or experimental design; (ii) included a comparator group comprising of unvaccinated pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
100
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(112 citation statements)
references
References 69 publications
11
100
0
1
Order By: Relevance
“…We agree that one explanation of these results may be the potential protective effect that influenza vaccination during pregnancy has on pre‐term birth. This protective effect of influenza vaccines against a range of adverse birth outcomes has been noted in other studies . An alternative explanation, however, may be reverse causation, whereby women with longer periods of gestation (≥ 37 weeks) have an increased opportunity to be vaccinated.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…We agree that one explanation of these results may be the potential protective effect that influenza vaccination during pregnancy has on pre‐term birth. This protective effect of influenza vaccines against a range of adverse birth outcomes has been noted in other studies . An alternative explanation, however, may be reverse causation, whereby women with longer periods of gestation (≥ 37 weeks) have an increased opportunity to be vaccinated.…”
supporting
confidence: 67%
“…This protective effect of influenza vaccines against a range of adverse birth outcomes has been noted in other studies. 2 An alternative explanation, however, may be reverse causation, whereby women with longer periods of gestation (≥ 37 weeks) have an increased opportunity to be vaccinated. In this study, data on the timing of vaccination were not available, but we are in the process of making a submission to the data custodians of the Victorian Perinatal Data Collection to enable capture and examination of these data.…”
Section: In Replymentioning
confidence: 99%
“…Firstly, it may indicate a potential beneficial effect of influenza vaccine received by pregnant women in reducing pre‐term birth (< 37 weeks' gestation). This is consistent with a recent systematic review and meta‐analysis that reported inactivated influenza vaccine to have a protective effect against pre‐term birth and low birth weight …”
supporting
confidence: 92%
“…I have limited my assessment to the most recent of the cited references, a systematic review, published in 2018. 6 Although stating that "Publications after May 2017 were not included", the review does not include two 5,7 of the three trials already published (the fourth 4 was published in September 2017), presumably because they were not placebocontrolled but active-controlled.…”
Section: Influenza Vaccination; Pregnant Women; Healthy Vaccinee Biasmentioning
confidence: 99%